Rumah Vertikal Ekologis di Surakarta dengan Fasilitas Pemberdayaan Ekonomi, Sosial dan Budaya Masyarakat Berpenghasilan Rendah - Purwanto, Dian, Ronim Azizah, ST., MT, Yayi Arsandrie, ST., MT (2016)
Seeing the condition of Surakarta in creasingly crowded, this has resulted in the price of land is increasingly scarce and expensive, this has resulted in Masyarakat Berpenghasilan Rendah (MBR) are not able to access the existing housing. Therefore, to solve need a vertical housing design in the form of rental flats are able to empower its residents, resulting in improved physical, economic, social and cultural residents. In order to realize development must pay attention with nature through Ecological Design approach. Looking at the various regulations and the idea of empowerment of economic, social and cultural MBR acquired site located at Ahmad Yani street. Site included in BWK III earmarked for settlements, trade and services. Land with area 8798.9 m2 close to Nusukan Market, Tertonadi Station and Rain Station. Flats standing on land is planned to accommodate 300 families MBR society. Users flats is quite MBR with many kinds of income backgrounds, so the function flats here is as a supporting the occupants. Community built to process waste and farming as an additional source of their income. Provides a garden as a catalyst of economic development. Flats are also given as a Koprasi to marketing of products produced by the community. To reduce planned expenditure on energyefficient buildings, low operational costs, and the building should be able to support itself. Guyub culture responds by providing a space of interaction. Flats are also given a mosque as control the behavior, character formation, as problem solving his community and as a melting pot of people around the residents of flats.